Monitoring cameras for violations in the use of personal protective equipment - Maulana Rasiddin, Muhammad; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2024)
Work Safety is an activity and effort to create a safe work environment, preventing all forms of accidents. To implement safe actions for workers, Personal Protective Equipment (PPE) is needed for workers to protect someone in doing their work. This Personal Protective Equipment (PPE) monitoring system begins by turning on the system by flowing the power supply to the system. Then the system is set via an access point via WiFi to be able to set the system on the microcontroller GUI. Then by selecting to activate "Motion Detect" and "Auto Upload" on the GUI, the system will automatically detect all movements within the range of the camera sensor. Furthermore, the system saves the video image of the object's movement in the memory on the system and will then be uploaded to a personal computer that has been set as an FTP server. After the personal computer saves the video image, the personal computer then sends the video image to the roboflow platform server. And when the video image is sent to the roboflow platform server, the video image is classified and labeled according to the dataset that the author created in the previous python programming. And finally, the video image that has been classified and labeled is stored again in the directory that has been specified in the programming